Intelligent finance and change management implications - Guo, Haochen; Polák, Petr (Springer London, 2023)
Change management is the embodiment of an enterprise's core competence. It provides competitive differentiation and effectively adapts to the ever-changing world. This paper explores the implications of intelligent finance on change management and provides insights into how organizations can effectively manage change to achieve the desired outcomes. The study examines the case of Ping An (Ping An Insurance (Group) Company of China, Ltd.), a leading insurance company in China that has successfully implemented intelligent finance and change management strategies. The paper begins with a literature review that provides an overview of the concept of intelligent finance, the relevance of change management in the context of intelligent finance, models, and frameworks for intelligent finance, and approaches to change management. The study then presents a case analysis of Ping An, including descriptive statistics, inferential statistics, regression analysis, and qualitative findings. The paper concludes with implications for practice and theory, contributions of the study, and recommendations for future research. Overall, this paper contributes to the growing literature on intelligent finance and change management and provides practical insights for organizations seeking to adopt intelligent finance.
Keywords: intelligent finance; management; strategies; organizations